Vaccination against HPV (Human Papilloma virus) for women - why is it still recommended and not obligatory in Poland? - Dubel, Julia; Dubel, Robert; Ruszel, Kinga; Czekaj, Aleksandra; Namroży, Natalia (Journal of Education, Health and Sport, 2022)
The most common sexually transmitted viral infection in the world is human papillomavirus (HPV). More than 100 types of HPV, both cutaneous and mucosal, have been characterized. Some HPV genotypes are the cause of cancer, which emphasizes the importance of infection prevention, including the use of vaccination against human papilloma virus.The following work aims to emphasize the role of vaccination in the prevention of HPV infection, discuss the transmission routes of this pathogen as well as diagnostics and treatment methods.